Isatis Glauca Subsp. Sivasica Extract Contributes to Diabetic Wound Healing Process via Increased Collagen and Nitric Oxide Content - Şule Coşkun Cevher; Kaan Kaltalıoğlu (Hittite Journal of Science and Engineering, 2021)
Isatis L. genus highly endemic and that is traditionally suggested for wound management in Turkey. In this study, we have reported the effect of I. glauca subsp. sivasica extract on diabetic wound healing process. A diabetic model was generated in Wistar rats using streptozotocin injection. Rats were divided into two main groups: control group and Isatis group. Full thickness excisional skin wounds were created by using a biopsy punch. The Isatis group was treated with single daily dose I. glauca subsp. sivasica extract (50 mg/kg). Rats were sacrificed day 3 or 7 after wounding. The dominant phenolic compounds identified with RP-HPLC-DAD from Isatis extract were the benzoic acid and vanillic acid. Isatis extract significantly accelerated wound healing process considering the wound closure rates (WCR). Moreover, the levels of collagen and nitric oxide were elevated on days 3 and 7 by Isatis administration in the diabetic wound tissue. These data suggest that, for the first time, I. glauca subsp. sivasica extract may have the potential to promote the impaired wound healing in patients with diabetes.